The construction of “Taishang zuo-zhe zhuxituan” in mandarin: a Cardiff grammar approach - Xiang, Dajun (Frontiers in Psychology, 2025)
Based on Cardiff Grammar, this paper studies the construction of “Taishang zuo-zhe zhuxituan” (“There is the presidium sitting on the stage”) in Mandarin, aiming to answer three key questions: (i) What Process type and Participant Roles are expressed by the construction? (ii) What is the functional syntactic structure of the construction? (iii) What are the functional motivations for using the construction? Guided by the principles of functional linguistic description, this study reveals that this construction realizes a Locational Relational Process, with two Participant Roles of Location and Carrier, which is different in meaning from similar constructions like “Zhuxituan zuo zaitaishang” (“The presidium sits on the stage”) and “Zhuxituan zaitaishang zuo-zhe” (“On the stage, the presidium sits”). The functional syntax of the construction is “S ^ P ^ C,” with the Subject conflated with Location, Complement with Carrier, and zhe following the verb zuo is an Aspect particle, which is part of the Predicator. The functional motivations of the construction include making taishang the Subject Theme, setting the scene for the discourse, and enhancing the state of existence of zhuxituan. This paper has implications for the study of other “location + V-zhe + thing” constructions in Mandarin and some similar linguistic phenomenon in other world languages.